Giving a voice to the Oppressed? The International Oral History Association as an academic Network and political Movement. - Arp, Agnès 1973-; Leo, Annette 1948-; Maubach, Franka 1974- (De Gruyter Oldenbourg, 2019)
Due to its internationality and interdisciplinarity, the International Oral History Association (IOHA), which was founded in the late 1970's, is one-of-a-kind in the academic landscape. Driven by the desire to democratize historical scholarship, its members wanted to "give a voice" to groups such as women, workers, migrants, or victims of political dictatorships who had not been heard up to that point. The contributions deal with the academic approaches and the political convictions of the previous generation
Description based on online resource; title from PDF title page (publisher's Web site, viewed 21. Dez 2019)
Keywords: International Oral History Association; Aufsatzsammlung